DEVELOPMENT ECONOMICS IN SMES BY GOVERNMENTS: A COMPARATIVE STUDY OF SMES HANDICRAFT IN MADAGASCAR AND INDONESIA - Raharimalala Narindraniaina Elisoa; Agus Hermawan; Puji Handayati (Yayasan Education and Social Center, 2022)
Each country's government appears to take their roles to push companies and enterprises to promote national economic, the existence of small and medium companies will help people find jobs, in other words, it can also raise a country's economy. Furthermore, the company encourages the government to assist businesses. This study focuses on the existing and growing SMEs Handicraft in Madagascar, an African country, and SMEs Handicraft in Indonesia, an Asian country; more specifically, it will investigate the roles and measures taken by local or national governments to develop small and medium enterprises. The research is being carried out on small and medium-sized enterprises, as well as handcraft businesses, in Ambositra, Madagascar, and Malang, Indonesia. The findings of this study indicate that SMEs in the handicraft sector are facing some challenges and difficulties. As a result, the governments of both countries are working actively to support handicraft as SMEs because they are part of national development tools, and they can also provide jobs for people